The right to a fair trial in constitutions of some Asean countries and Vietnam: a comparative analysis - Truong, Ho Hai (Đại học Quốc gia Hà Nội, 2020)
The right to a fair trial is one of the basic human rights, which has been recognized by international human rights law and has become one of the particularly important principles in the proceedings of rule of law. In fact, Asian countries have been implementing this principle both in terms of the provisions of the Constitution and the actualization of those provisions in practice. The evaluation for the provisions of the right to a fair trial in the Constitution and the practical implementation of China, South Korea, Japan and Indonesia will provide valuable lesson for Vietnam in the process of judicial reform to meet the requirements of building the socialist rule of law in the current context.